NUMERICAL ANALYSIS OF STRENGTH OF REAR BRAKE HOLDER FLAT ON THE MOTOR CYCLE DUE TO IMPACT LOAD - Zulfikar Zulfikar; Bobby Umroh; Amrinsyah Amrinsyah; Fadly A Kurniawan (Universitas Medan Area, 2018)
Brake is one of vital motorcycle element, which serves as a speed reduction mechanism. This section reinforced with retaining plate which serves to hold the wheels when braking process occurs. Research on the plate strength is still rarely found. Stress distribution that occurs on the plate due to shock loads is also not well known. Therefore, this study aims to obtain the strength retaining plate with a numerical analysis of the distribution of stress and deformation which occur on plate. Research done in two ways, experimentally and numerical simulations. Experimentally, direct measurements on the amount of stress that occurs on the plate. The research was done by putting strain gage on the connection plate and brake. In simulation, using Nastran software with the primary data based on the results of the experimental measurements. Based on the results of the numerical analysis of the stress distribution that occurs is obtained that the maximum stress distributed around the staging area in direct contact with the brake. Therefore, motorists should be aware that section and provide additional anchoring structure to further strengthen the structure of the retaining plate rear brake.